Technological Mapping of Patents Related to Cloud Gaming - Ribeiro, Vianney de Oliveira (2024)
Digital games have played a fundamental role in technological evolution over the past few decades, driving innovations that extend beyond entertainment and impact various industries. Among these innovations, cloud gaming technology emerges as a significant transformation in the video game market, allowing graphically complex games to be executed directly in the cloud, eliminating the need for local installation or high-performance hardware. This advancement results from the convergence of multiple technological areas, such as high-speed networks and cloud computing, and is reflected in the significant growth of patents related to cloud gaming, especially since 2015. China, in particular, stands out as a leader in the sector, accounting for 42.99% of the identified patents, with 10 of the 20 largest patent holders based in the country. These data highlight not only the growing importance of cloud gaming but also China's central role in shaping this new global landscape.